Assistance in Determining Cost of Production for Eni Taylor - Rifdah Aufa Adilah; Kautsar Riza Salman (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
The problem to be raised in this research is the calculation of Eni Taylor's Cost of Production (HPP). Due to the development of the times, many people prefer to buy clothes in shops or rent from rental places, making it difficult for the tailor profession to survive at this time. Eni Taylor made collaborative efforts with boutiques and places for renting wedding uniforms, traditional clothes to maintain the business, but Eni Taylor had difficulty determining the HPP of each product. This research was conducted in Kramatinggil Village, Kab. Gresik with the observation method, namely observing the production activities carried out by Eni Taylor and the interview method by taking the required data such as HPP elements by asking questions related to this matter. The steps taken to solve this problem are to design a template to make a COGS report. It is hoped that this research will benefit Eni Taylor and the surrounding environment.